Stability Satisfied Design and Construction of Excavated Soil Dumps in a Soft Soil Region in China - Wang, Jin-Nan; Xu, Hui; Zhan, Liang-Tong; Li, Sheng-Zhi; Wang, Lu-Nan (Frontiers in Earth Science, 2022)
Dumping is the main disposal method of the excavated soil from underground engineering in China, however, due to a lack of construction experience and technical standards, the landslide disasters often occurred during rapid dumping of excavated soil in soft soil regions. In this paper, the geotechnical property tests were conducted on the excavated soil from a foundation engineering site in Hangzhou, where the soil would be used to construct a piled mountain. On this basis, a numerical study was carried out to investigate the effects of the design parameters (heap height, slope gradient) and construction parameters (layer thickness, heap speed) on the dump stability and failure mode. The results show that the safety factor of the excavated soil dump decreases with the increasing heap height, slope gradient, layer thickness and heap speed. The potential slide surfaces are toe circle, and compared to layer thickness and heap speed, the heap height and slope gradient have more remarkable influence on the depth and area of potential slide mass. The limit heap height increases with a decrease in slope gradient and the limit heap speed decreases with an increase in layer thicknesses. Under the premise of ensuring the slope stability, the optimal design and construction parameters were obtained, i.e., heap height 28 m, slope gradient 1:2.75, layer thickness 1.0 m and heap speed 0.50 m/day. Compared to the original design, the storage capacity increases by 20.01% and the construction duration decreases by 30.25% in the optimal design.